2018
DOI: 10.3390/su10030680
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cost–Quality Trade-Off Model for Differentiating Presale Housing Quality Strategies

Abstract: Housing quality (HQ) has been a long-standing concern for both developers and homebuyers. Currently, HQ depends on the expected profit and subjectivity of the developers, and homebuyers only have a passive choice of whether to accept housing with such quality. Asian housing supply markets have largely adopted the presale housing system. Under this system, developers are able to verify future occupants before commencing construction, enabling them to provide customized designs and differentiated quality items i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Kebriyaii et al developed a MOMPM for the trade-off of the time, cost, and quality scheduling problems in construction projects considering the time value of money, which is decreased over a long period and is a very important matter [38]. Research on optimization in this area has been carried out previously, which can be mentioned [39,40].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Kebriyaii et al developed a MOMPM for the trade-off of the time, cost, and quality scheduling problems in construction projects considering the time value of money, which is decreased over a long period and is a very important matter [38]. Research on optimization in this area has been carried out previously, which can be mentioned [39,40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Juan and Lin proposed a trade-off of the cost and quality model using a genetic algorithm [40]. Eirgash et al identified a model using a multi-objective learning-based optimization algorithm for project-scheduling optimization [41].…”
Section: Literature Reviewmentioning
confidence: 99%